Circ-ATP8A2 promotes cell proliferation and invasion as a ceRNA to target EGFR by sponging miR-433 in cervical cancer - Ding, Lin; Zhang, Hongtao (Gene, 2019)
Cervical cancer (CC), a common gynecological carcinoma, is a serious threat to women's health. The dysregulation of circular RNAs (circRNAs) is associated with the pathogenesis of cervical cancer. Therefore, we explored the role of circ-ATP8A2 in CC cell development and progression. Circ-ATP8A2 profiles in CC specimens and cells were detected using real-time PCR. In addition, cell counting kit-8 (CCK-8), acridine orange/ethidium bromide (AO/EB), flow cytometric, and Transwell experiments were carried out on HeLa and SW756 cells to determine cell proliferation, apoptosis, migration and invasion. Furthermore, the mechanism of circ-ATP8A2 was explored by dual-luciferase reporter system. Circ-ATP8A2 was significantly enhanced in CC specimens and cells. Knockdown of circ-ATP8A2 inhibited cell proliferation, migratory and invasive capacities and increased apoptotic cells. Ectopically expressed circ-ATP8A2 induced the opposite effects. For the mechanism exploration, circ-ATP8A2 sponges miR-433 to release its suppression on epidermal growth factor receptor (EGFR) expression at post-transcriptional level. What's more, circ-ATP8A2 could promote cell progression by miR-433/EGFR axis in CC cells. Collectively, this work might offer a potential treatment target for CC. Unlabelled TableAO/EBacridine orange/ethidium bromideCCcervical cancerCCK-8cell counting kit-8circRNAscircular RNAsEGFRepidermal growth factor receptorPIpropidium iodide •Circ-ATP8A2 expression is elevated in cervical cancer tissues and cells.•Circ-ATP8A2 exerts oncogenic properties in cervical cancer cells.•High expression of Circ-ATP8A2 correlates with adverse clinical features and poor prognosis.•Circ-ATP8A2 acts as a sponge of miR-433 and releases its suppression on EGFR.•Circ-ATP8A2 promotes cell progression by miR-433/EGFR axis in cervical cancer cells.